“We Can All Learn Together so We’re All on the Same Page”: Impact of a Learning Essential Approaches to Palliative Care Hospital Course on Hospitalists’ Practice - Ashlinder Gill; Sarah Romeril; Lynn Meadows; Alison Flanagan; Ashwak Rhayel; Michael Panza; Christopher Klinger; Narisa Duboff; Jose Pereira; Joan Bellaire (Palliative Medicine Reports)
Background: In Canada, access to palliative care varies across jurisdictions. Many health care professionals lack core palliative care competencies. To help build capacities, a pilot education program was conducted at a community hospital in Southwestern Ontario (Canada). Using Pallium Canada’s Learning Essential Approaches to Palliative Care (LEAP) Hospital course, generalist hospital physicians participated in this initiative. The purpose of this investigation was to explore the impact of the LEAP Hospital course on physician attitudes, comfort, and care delivery. Methods: Within a Plan-Do-Study-Act framework, a mixed-methods design summarized post-course evaluations, commitment to change (CTC) statements, and interviews with learners and hospital staff. Participants completed pre-course knowledge and post-participation surveys. Group and individual interviews were conducted with learners and staff who practiced alongside LEAP learners. Descriptive statistics were completed for aggregate survey data. Thematic analysis was conducted to summarize learner and staff experiences. Results: Twenty-nine physicians completed the LEAP Hospital course. Ninety-six CTC statements identified improvements in symptom management and communication. Sixteen participants participated in interviews. Learners and hospital staff noted the impact courses had on symptom and disease management and enhanced communication when discussing goals of care. Learners valued case-based learning and connecting with peers who are often siloed in practice. Participants also noted the inclusion of allied health for greater collaboration. Conclusions: LEAP Hospital courses enhanced knowledge and skills and incorporated a greater palliative approach to care. Establishing a community of practice to address educational needs and strategies should be considered while supporting the inclusion of new graduates and hires.